2021
DOI: 10.1002/prep.202000090
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Oxygen Balance of Energetic Composites: Crystallization of ADN/Secondary Explosives Mixtures by Spray Flash Evaporation

Abstract: New energetic composites with enhanced reactive performances while allowing the safe handling according to their sensitivity thresholds are presented. This paper combines different approaches: the intimate contact between the compounds, the particle size reduction and the processing of composite materials to maintain the oxygen balance close to zero. The Spray Flash Evaporation process enables the fast crystallization at the submicron scale by combining an oxidizer, ammonium dinitramide ADN and two secondary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…This phenomenon was consistent with the ignition delay time results. The reason for the improvement in the burning intensity by adding ADN is that the energetic salt possesses positive oxygen balance [ 42 ]. From the ignition delay time and combustion flame in the burning process, it can be seen that the combustion performance of NC-based composite fibers can be improved significantly by the addition of ADN.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon was consistent with the ignition delay time results. The reason for the improvement in the burning intensity by adding ADN is that the energetic salt possesses positive oxygen balance [ 42 ]. From the ignition delay time and combustion flame in the burning process, it can be seen that the combustion performance of NC-based composite fibers can be improved significantly by the addition of ADN.…”
Section: Resultsmentioning
confidence: 99%
“…Oxygen balance: Oxygen balance is defined as the amount of oxygen in default or in excess with regard to what is required for a completed combustion, and it is important indicator to determine the potential of an energetic material mostly explosives and oxidants, which require a positive oxygen balance, but the default in oxygen balance in these latter could be covered by binders or fuel that have excess of oxygen in their formulations. 42,43 As seen in Table 2, the oxygen balance of DNPH-Bz is superior to that of SC-Bz and almost akin to that of GAP-diol. What is more, the oxygen balance of the synthesized polymers could be enhanced by the nitration of the polymer backbone without amending the neither the sensibility nor the stability of the modified polymer.…”
Section: Calorific Powermentioning
confidence: 94%
“…Lobry et al [ 90 ] reported an innovative work on the spray flash evaporation of an oxidizer ammonium dinitramide (ADN) on two secondary explosives RDX and HMX. A liquid solution containing ADN and explosive was superheated in atomization chamber.…”
Section: Preparation Methods For Csesmentioning
confidence: 99%